2008
DOI: 10.1002/jssc.200700638
|View full text |Cite
|
Sign up to set email alerts
|

Selective determination of catechin, epicatechin and ascorbic acid in human urine using chiral capillary electrophoresis

Abstract: Chiral CE was successfully applied to the separation and quantification of catechin, epicatechin and ascorbic acid in some commercial drinks and human urine. Analysis involved the separation of analytes in less than 5.0 min at 240 nm with an untreated fused-silica capillary under hydrodynamic injection mode. The running buffer consisted of 50 mM borate buffer with 3 mM beta-CD at pH 8.35. Detection limits for catechin, epicatechin and ascorbic acid were 0.028, 0.011 and 0.004 microg/mL, respectively. Linearity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…These include two anthelmintic drugs, albendazole and mebendazole. Albendazole becomes oxidized to chiral albendazole sulfoxide [95][96][97][98], and mebendazole is hydroxylated [110]. Analysis of plasma from echinoccocosis patients undergoing pharmacotherapy with these drugs revealed that the two metabolic steps are enantioselective in man.…”
Section: Assessment Of Stereoselective Pharmacokinetics and Drug Metamentioning
confidence: 98%
“…These include two anthelmintic drugs, albendazole and mebendazole. Albendazole becomes oxidized to chiral albendazole sulfoxide [95][96][97][98], and mebendazole is hydroxylated [110]. Analysis of plasma from echinoccocosis patients undergoing pharmacotherapy with these drugs revealed that the two metabolic steps are enantioselective in man.…”
Section: Assessment Of Stereoselective Pharmacokinetics and Drug Metamentioning
confidence: 98%
“…The wide use of UV detection was also true for food and food contaminants analyses 85, 177, 190, 196–287. However, increasing also were those exploiting CE‐MS 141, 143–145, 146, 148, 288–303.…”
Section: Detection Strategiesmentioning
confidence: 99%
“…El-Maali's group [28,29] recently published two papers using β-CD as a chiral selector. (+)-Catechin and (−)-epicatechin were baseline-separated and quantified in aqueous and plasma samples [28].…”
Section: Cyclodextrins As Chiral Selectorsmentioning
confidence: 99%
“…The method was applied to a plasma sample after ingestion of green tea, and 2 h after ingestion, 17.4% of catechin and 1.8% of epicatechin, with respect to their concentration in the tea, were found unchanged in plasma. The same enantiomers, along with ascorbic acid, were separated and quantified in urine in the next study by this group [29]. The method developed was validated in terms of selectivity, accuracy, precision, linearity, LOD, LOQ, and robustness.…”
Section: Cyclodextrins As Chiral Selectorsmentioning
confidence: 99%